Comparative evaluation of unfixed and fixed human neutrophils for determination of antineutrophil cytoplasmic antibodies by indirect immunofluorescence. Issue 8 (August 1997) - Yang, P
Abstract : BACKGROUND: Antineutrophil cytoplasmic antibodies (ANCAs) are found in the sera of patients with vasculitides and ulcerative colitis. Using indirect immunofluorescence on ethanol fixed neutrophils, ANCAs can be divided into two types: those that give a cytoplasmic staining pattern (C-ANCA) and those that give a perinuclear staining pattern (P-ANCA). Some studies have indicated that the perinuclear staining pattern might be an artefact of alcohol fixation. AIMS: To observe any changes seen in the ANCA staining pattern using indirect immunofluorescence on unfixed neutrophils or neutrophils that had been fixed by ethanol, acetone, or paraformaldehyde. In addition, the effects of the different fixation methods on the sensitivity of the indirect immunofluorescence test were evaluated. METHODS: Twenty one sera from patients with ulcerative colitis and 19 from healthy controls were studied. In addition, 17 sera from patients with vasculitides, including eight with proteinase 3 (PR 3) positive C-ANCA and nine with myeloperoxidase (MPO) positive P-ANCA were included in the study. Antineutrophil cytoplasmic antibodies were analysed by indirect immunofluorescence on unfixed neutrophils or cells fixed by ethanol, acetone, or paraformaldehyde. RESULTS: All the ulcerative colitis associated ANCA positive sera presented a peri-nuclear staining pattern on both unfixed and fixed cells. The acetone and paraformaldehyde fixations decreased the ulcerative colitis P-ANCA titres. Paraformaldehyde fixation also decreased the MPO positive P-ANCA titres. In indirect immunofluorescence, the staining patterns of all the eight PR 3 positive C-ANCA sera and eight of the nine MPO positive P-ANCA sera did not change, even if unfixed or fixed cells were used. CONCLUSIONS: The ANCA staining patterns are not affected by the fixation method used, and are the same as when unfixed neutrophils are used; this suggests that the P-ANCA pattern is not an artefact of alcohol fixation. Furthermore, this study confirms that on ethanol fixed neutrophils, the antigen of ulcerative colitis associated P-ANCA is better exposed than on acetone or paraformaldehyde fixed cells.